Cryptic Methane-Cycling by Methanogens During Multi-Year Incubation of Estuarine Sediment - Kevorkian, Richard T.; Sipes, Katie; Winstead, Rachel; Paul, Raegan; Lloyd, Karen G. (Frontiers in Microbiology, 2022)
As marine sediments are buried, microbial communities transition from sulfate-reduction to methane-production after sulfate is depleted. When this biogenic methane diffuses into the overlying sulfate-rich sediments, it forms a sulfate-methane transition zone (SMTZ) because sulfate reducers deplete hydrogen concentrations and make hydrogenotrophic methanogenesis exergonic in the reverse direction, a process called the anaerobic oxidation of methane (AOM). Microbial participation in these processes is often inferred from geochemistry, genes, and gene expression changes with sediment depth, using sedimentation rates to convert depth to time. Less is known about how natural sediments transition through these geochemical states transition in real-time. We examined 16S rRNA gene amplicon libraries and metatranscriptomes in microcosms of anoxic sediment from the White Oak River estuary, NC, with 3 destructively-sampled replicates with methane added (586-day incubations) and 3 re-sampled un-amended replicates (895-day incubations). Sulfate dropped to a low value (~0.3 mM) on similar days for both experiments (312 and 320 days, respectively), followed by a peak in hydrogen, intermittent increases in methane-cycling archaea starting on days 375 and 362 (mostly Methanolinea spp. and Methanosaeta spp., and Methanococcoides sp. ANME-3), and a methane peak one month later. However, methane 13C values only show net methanogenesis 6 months after methane-cycling archaea increase and 4 months after the methane peak, when sulfate is consistently below 0.1 mM and hydrogen increases to a stable 0.61 ± 0.13 nM (days 553-586, n = 9). Sulfate-reducing bacteria (mostly Desulfatiglans spp. and Desulfosarcina sp. SEEP-SRB1) increase in relative abundance only during this period of net methane production, suggesting syntrophy with methanogens in the absence of sulfate. The transition from sulfate reduction to methane production in marine sediments occurs through a prolonged period of methane-cycling by methanogens at low sulfate concentrations, and steady growth of sulfate reducers along with methanogens after sulfate is depleted.